Karol Marks a powstanie styczniowe - Ciolkosz, Adam (Londyn : Democratic Press and Liberty Publications, 1963)
Bibliotheek Camille Huysmans
Dedicator: Ciolkosz, Adam, dedicatee: Huysmans, Camille
Brochure handelt over de januari-opstand in 1863 in Polen
Pools
Brochure
Keywords: Marx, Karl; 19e eeuw; revoluties; Polen